The effects of eccentric cycling on vascular reactivity - Gomez, Manuel; Montalvo, Samuel; Conde, Daniel; Ibarra-Mejia, Gabriel; Gurovich, Alvaro N. (Frontiers in Physiology, 2025)
PurposeEccentric cycling has gained attention as a novel exercise modality that increases muscle performance at lower metabolic demand, which could enhance cardiovascular rehabilitation. However, endothelial function response to eccentric cycling (ECC) has yielded contradictory results. Therefore, the purpose of this study was to determine the effect of 30 min of moderate-intensity cycling ECC on endothelial function.MethodsA total of 15 (9 females, 6 males) young, apparently healthy participants were recruited for two laboratory visits. First, a maximum oxygen consumption (VO2max) and blood lactate (BLa) threshold were measured to determine moderate workload intensity, followed by a familiarization stage on an ECC ergometer. During the second visit, a 30-min of moderate ECC was performed 72 h after the first visit. Endothelial function was measured via Flow-Mediated Dilation (FMD) pre- and post-exercise bout. FMD was calculated following traditional recommendations and adjusting for exercise-induced endothelial shear stress (ESS), utilizing the same pre-exercise baseline artery diameter for post-exercise FMD calculations.ResultsThere was a significant increase in endothelial function (p = 0.037) when adjusting pre-exercise baseline diameter to adjust for ESS, but when utilizing the traditional method no change in endothelial function was observed.Conclusion30-min of moderate ECC showed a significant improvement in endothelial function when accounting for exercise-induced ESS. These results support the use of the pre-exercise baseline diameter when calculating post-exercise FMD to avoid the exercise-induced ESS or muscle metabolites effects on post-exercise artery diameter.